Ketogenic therapy in childhood and adolescence: recommendations of the Brazilian experts group - de Brito Sampaio, Letícia Pereira; Henriques-Souza, Adélia Maria de Miranda; Lin, Katia; Neri, Lenycia de Cassya Lopes; Inuzuka, Luciana Midori; Uchôa, Ludmila Inácio de Lima; Gregório, Marcela Marques de Oliveira; Guilhoto, Laura Maria; Montenegro, Maria Augusta; Lunardi, Mariana; Veiga, Marielza; de Lima, Patricia Azevedo; Braatz, Vera (Arquivos de Neuro-Psiquiatria, 2023)
Ketogenic dietary therapies (KDTs) are a safe and effective treatment for pharmacoresistant epilepsy in children. There are four principal types of KDTs: the classic KD, the modified Atkins diet (MAD), the medium-chain triglyceride (MCT) diet, and the low glycemic index diet (LGID). The International Ketogenic Diet Study Group recommends managing KDTs in children with epilepsy. However, there are no guidelines that address the specific needs of the Brazilian population. Thus, the Brazilian Child Neurology Association elaborated on these recommendations with the goal of stimulating and expanding the use of the KD in Brazil.
Keywords: Diet, Ketogenic; Drug Resistant Epilepsy; Neurology; Brain Diseases